Who are the farm shop buyers? A case study in Naumburg, Germany. Issue 2 (5th February 2018) - Bavorova, Miroslava; Traikova, Diana; Doms, Juliane
Abstract : Purpose: The purpose of this paper is to examine the factors that influence consumers' shopping behaviour from farm shops. Design/methodology/approach: The study is based on the theory of planned behaviour (TPB). Data were gathered in 2015 and 2016 via a quantitative written survey of 135 pedestrians in a structured questionnaire in Naumburg, East Germany. The authors use the variance-based, partial least squares subfamily of structural equation models for the analysis, allowing the authors to investigate the causes of the formation of attitudes, social norms and perceived behavioural control (PBC) related to buying from farm shops. Findings: Seen through the TPB prism, the most powerful explanatory construct in the model is PBC. This is followed by favourable attitudes towards buying at the farm gate. Interestingly, the injunctive norms construct is not significant, while the descriptive norms construct is. This means that the observed behaviour of relevant peers is more strongly linked to buying at the farm gate than what significant others want respondents to do. Originality/value: Farm shops are one of the innovative distribution channels used by farmers to sell regional products directly to consumers. Studies that analyse the factors that have an effect on consumer behaviour when buying food from farm shops are very scarce. This paper fills this gap and the findings have implications for communications to consumers and labelling.